Recent advances in spray drying relevant to the dairy industry: A comprehensive critical review. Issue 15 (17th November 2016) - Schuck, Pierre; Jeantet, Romain; Bhandari, Bhesh; Chen, Xiao Dong; Perrone, Ítalo Tuler; de Carvalho, Antônio Fernandes; Fenelon, Mark; Kelly, Phil
ABSTRACT: Milk is extremely perishable, and yet it has to be preserved for later consumption. In this view, membrane filtration, vacuum concentration lactose crystallization, homogenization, and spray-drying dehydration are valuable techniques to stabilize most dairy ingredients. Considering the increasing development of dairy trade, there is a need for the dairy industry to improve its understanding of how these concentration and spray-drying processes affect the quality of the resulting dairy powders, so to control it. However, the residence time of the droplet and the powder in the spray dryer is so short that it is very difficult to implement studies on the mechanisms of the structural changes in the protein without fundamental research into the process/product interactions. Moreover, several authors have reported the crucial and specific role of dairy components in the mechanisms of water transfer during drying and rehydration. The aim of this paper is to review the present and recent advances in knowledge and innovations, on the properties of spray-dried dairy products, on the modeling and simulation of water transfer processes (drying and rehydration), and on spray-drying equipment and energy consumption.